2001
DOI: 10.1007/pl00000887
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of glucose transporters during chick embryogenesis

Abstract: The patterns of Glut1 and Glut3 glucose transporter protein and mRNA expression were assessed during embryogenesis of chicken brain and skeletal muscle, Glut4 protein levels were also evaluated in skeletal muscle and heart, and Glut1 was examined in the developing heart and liver. Glut1 protein expression was detectable throughout brain ontogeny but was highest during early development. Glut1 mRNA levels in the brain remained very high throughout development. Glut3 protein was highest very early and very late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
4
25
1
2
Order By: Relevance
“…GLUT1 is already highly expressed in bovine oocytes [32] suggesting that foetal cells are able to take up glucose and use it as an energy source from the earliest stages. As in cattle (present study), GLUT1 expression has also been shown to be maximal in early foetal life and to decrease steadily throughout gestation in the heart and skeletal muscle of the chicken [33]. Some species-specific regulation has, however, been demonstrated: GLUT1 expression at both the protein and mRNA levels is indeed shown to decrease after birth in the rat heart [11] and in the brain, lung, liver and kidney of rodents [34][35][36], whereas the GLUT1 level does not change in the skeletal muscle and adipose tissue of Holstein male calves from birth to 12 months of age [37].…”
Section: Ontogenesis Of Glucose Transporterssupporting
confidence: 81%
See 1 more Smart Citation
“…GLUT1 is already highly expressed in bovine oocytes [32] suggesting that foetal cells are able to take up glucose and use it as an energy source from the earliest stages. As in cattle (present study), GLUT1 expression has also been shown to be maximal in early foetal life and to decrease steadily throughout gestation in the heart and skeletal muscle of the chicken [33]. Some species-specific regulation has, however, been demonstrated: GLUT1 expression at both the protein and mRNA levels is indeed shown to decrease after birth in the rat heart [11] and in the brain, lung, liver and kidney of rodents [34][35][36], whereas the GLUT1 level does not change in the skeletal muscle and adipose tissue of Holstein male calves from birth to 12 months of age [37].…”
Section: Ontogenesis Of Glucose Transporterssupporting
confidence: 81%
“…In the present study, the higher expression of GLUT4 from 8 months of foetal age was concomitant with lower plasma glucose levels in the foetus, suggesting that insulin stimulation of glucose uptake through GLUT4 does occur. However, unlike in cattle (present study) and rodents [11,28], GLUT4 protein and mRNA appear to be absent from the chick heart and skeletal muscle [33], which may be explained either by differences in the sensitivity of the techniques used or by differences in the biological maturity at birth between the different species [13].…”
contrasting
confidence: 65%
“…GLUT3 in the brain increased throughout the stages of development, but was absent in skeletal muscle. This study also revealed that GLUT4 was absent in chicken heart and skeletal muscle [67].…”
Section: Glut14/ Slc2a14supporting
confidence: 62%
“…Additionally, higher rates of insulin infusion and higher plasma insulin concentrations might increase production of and/or translocation of other glucose transporter isoforms, including GLUT1, which our previous studies did show was responsive to insulin with increased expression and abundance, and GLUT3, which has been found in fetal skeletal muscle (6,14,29,(33)(34)(35)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 91%